Trading water: virtual water flows through interstate cereal trade in India. (1st December 2020) - Harris, Francesca; Dalin, Carole; Cuevas, Soledad; N R, Lakshmikantha; Adhya, Tapan; Joy, Edward J M; Scheelbeek, Pauline F D; Kayatz, Benjamin; Nicholas, Owen; Shankar, Bhavani; Dangour, Alan D; Green, Rosemary
Abstract: Cereals are an important component of the Indian diet, providing 47% of the daily dietary energy intake. Dwindling groundwater reserves in India especially in major cereal-growing regions are an increasing challenge to national food supply. An improved understanding of interstate cereal trade can help to identify potential risks to national food security. Here, we quantify the trade between Indian states of five major cereals and the associated trade in virtual (or embedded) water. To do this, we modelled interstate trade of cereals using Indian government data on supply and demand; calculated virtual water use of domestic cereal production using state- and product-specific water footprints and state-level data on irrigation source; and incorporated virtual water used in the production of internationally-imported cereals using country-specific water footprints. We estimate that 40% (94 million tonnes) of total cereal food supply was traded between Indian states in 2011–12, corresponding to a trade of 54.0 km 3 of embedded blue water, and 99.4 km 3 of embedded green water. Of the cereals traded within India, 41% were produced in states with over-exploited groundwater reserves (defined according to the Central Ground Water Board) and a further 21% in states with critically depleting groundwater reserves. Our analysis indicates a high dependency of Indian cereal consumption on production in states with stressed groundwater reserves. Substantial changes in agricultural practices and land use may be required to secure future production, trade and availability of cereals in India. Diversifying production systems could increase the resilience of India's food system.